ANALISIS PERAN STAKEHOLDERS DALAM PENGEMBANGAN DESA WISATA JATIREJO, KECAMATAN GUNUNGPATI, KOTA SEMARANG - Phytaloka Gayatri, Nyken Ayu; Warsono, Hardi; Santoso, Slamet (Journal of Public Policy and Management Review, 2024)
One of the principles of sustainable development is the concept of tourism village development. Through the Decree of the Mayor of Semarang Number: 556/819 concerning the Designation of Semarang City Tourist Villages, Jatirejo Tourist Village is one of the tourist villages in Semarang City which has quite promising potential for development. Development certainly involves the contribution of various stakeholders involved. This research aims to identify the role of stakeholders and analyze the inhibiting and driving factors in the development of the Jatirejo Tourism Village. This research uses a qualitative descriptive method with data collection through observation, interviews and documentation. The research results show that the roles of the stakeholders involved consist of primary stakeholders which include nongovernmental organizations, local residents, and visitors/tourists and secondary stakeholders which consist of the government and academics. Supporting factors consist of values (individuals, organizations, policies and professionalism), communication, trust and policies, while inhibiting factors consist of lack of competence and participation of Pokdarwis members, lack of participation of Pokdarwis members and local residents, less than optimal marketing of tourism products. Recommendations that can be given are to increase the capacity of development and training activities, build accountability regarding the operation of the bureaucracy so that it is easy for local residents to understand, develop infrastructure, and develop communication media for the promotion of tourist villages.